المتغيرات الدولية وانعكاساتها على السياسات التسويقية "دراسة تطبيقية على صناعة الغزل والنسيج في اللاذقية" - هرمز نور الدين; ناصر محمد جودت; سلمان غيداء إبراهيم (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول البحث أثر المتغيرات الدولية على السياسات التسويقية في سورية ودراسة واقع بعض منشآت الغزل والنسيج المتردي, وتحليل هذا الوضع بهدف التعرف على إيجابيات ونقاط الضعف فيها ووضع المقترحات لمعالجتها، في ظل عدم وجود اهتمام كاف بالتسويق, وعدم القيام بدراسة الأسواق أو إعطاء أي أهمية لبحوث التسويق، وعدم الأخذ بعين الاعتبار ما يجري حولنا من متغيرات تؤدي إلى مواجهة حقيقية مع الآخرين وتضع منشآتنا أمام منافسة حادة وقوية. إذ تضمن البحث مجموعة من الجوانب وأهمها: التعرض لبعض المتغيرات السياسية والاقتصادية والتقنية والاجتماعية. واقع التسويق في بعض المنشآت الاقتصادية كالغزل والنسيج في اللاذقية. أثر هذه المتغيرات على التسويق في هذه المنشآت ومحاولة وضع سياسة علمية مدروسة لمواجهة التحديات القائمة. This research studies the impact of international changes on marketing strategies in Syria, especially the deteriorating situation of some spinning and textile institutions. The main objective of analyzing this situation is to identify its positive and negative aspects and to put forward suggestions to handle these weaknesses. The absence of enough interest in marketing, scarcity of market studies, giving no priority to marketing research, nor taking the changes around us into account may lead to confrontation with others and place our plants on a fierce competition course. This study includes many points, some of which are: Dealing with some political, economic, technical, and social changes. The marketing status in some economic institutions such as spinning and textile plant in Lattakia. The effect of these changes on marketing and formalizing a well-planned scientific policy geared to facing present challenges